Correlation Between Maternal Knowledge About Danger Sign and Antenatal Care (ANC) Visit Compliance in The Health care Center - Devi Wahyuningsih; Kris Linggardini (UM Purwokerto Press, 2022)
Background: Pregnancy problems, which can manifest as pregnancy danger of sign or symptoms that the suggest the mother or baby is at risk, are one of the causes of the high maternal death rate. Objective: This study aims to determine the raltionship between a mother’s knowledge about pregnancy danger sign and ANc visit compliance at Lakbok Health Care. Methods: This study is type of quantitative research of Cros-Sectional. This research was conducted at the Lakbok Health Care Center in June 2021. This study used a total sampling of 35 respondents using correlation test. Results: The finding revealed that the mother’s understanding of pregnancy danger symptomps in the Lakbok Health Care Center area was only partially sufficient (68,6%). Pregnant women in the Lakbok Health Center region were mainly compliant with antenatal care (54,3%). The correlation test revealed that there was a relationship between maternal understanding of pregnancy danger sign and ANC visits with a p-value 0,027. Conclusion: There is relationship between Mother’s Knowledge of Pregnancy danger sign with ANC Compliance at Lakbok Health Care Center.